Influence of Compensation on Special Needs Educators’ Job Satisfaction in Special Schools for The Learners with Hearing Impairment in Kenya - Nyongesa, Gregory (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2024)
Effective teaching and learning to achieve the educational goals require satisfied teachers, yet, most of the teachers in Kenya indicate lack of job satisfaction with their work. The rising numbers of special needs educators exiting from special schools for the Hearing Impaired and the frequent strikes are the possible indicators. This study examined the influence of Compensation on teacher job satisfaction among the Special Educators in Public Special Primary Schools for the Hearing Impaired in Kakamega County Kenya. This study employed the Two Factor Theory of Herzberg. The study adopted multiple case study design. The study was carried out in Special Primary Schools for the HI in Kakamega County. The target population was 59 respondents, which comprised of 4 headteachers, 4 deputy headteachers, 47 classroom teachers and 3 curriculum support officers for special needs drawn from each of the sub counties where the special schools for the HI is located. The sample size was a total of 58 participants. Saturated sampling technique was used. Interview schedules, Focus Group Discussions and document analysis were used for data collection. The study adopted thematic analysis to generate the findings of the study. The study found out that Special educators were not satisfied with the salary and allowances that they were given by the Teachers Service Commission (TSC) Fringe benefits and incentives are also highly valued by the special educators.